Urso contra “MagraSS”: Pistas para um processo criativo em diálogo com o Teatro Documentário e a Autoficção - Holanda, Walmick de; Wilker, Francis (Farol, 2022)
This article investigates traces for a process of scenic creation from a real situation of fatphobia experienced/suffered by one of the authors. The investigation is pupported by the notion of the creative process, understood as a constructive path that involves movement, interaction and transformation. From thes perspective, the reflection establishes dialogues with the propositions of Documentary Theater and Autofiction/Self-Writing, seeking directios for creative elaboration.